The Role of Traditional Islamic Boarding School-Based Islamic Studies as Radicalism and Intolerance Flow’s Blocking Agent - Suryadi Suryadi; M. Mansur (UIN Sunan Kalijaga Yogyakarta, 2017)
In Indonesia, the attitude of radicalism and intolerance within Islam has flourished over the last few decades. There are several factors that encourage the emergence of it. One of them is the waning of Islamic Studies in various educational institutions today. As a result, Islam is only understood to be a matter of aqeedah and worship. Basically, many studies have been conducted to tackle radical and intolerant behavior with various approaches: social, political, economic, etc. In this paper, one offer of solutions through Islamic Studies in traditional Islamic Boarding School education institutions will be discussed. The findings in the field stated that the curriculum applied in Islamic Boarding School became one of the significant factors in the efforts of deradicalization. It can not be separated from the open-minded learning method and various teaching materials of Islamic Boarding School that made students to be familiar with diversity.[Di Indonesia, sikap radikalisme dan intoleranisme dalam Islam tumbuh subur selama beberapa dekade terakhir. Ada beberapa macam faktor yang mendorong munculnya hal tersebut. Salah satu di antaranya adalah memudarnya kajian Islamic Studies dalam berbagai lembaga pendidikan dewasa ini. Akibatnya, Islam hanya dipahami sebatas persoalan akidah dan ibadah saja. Pada dasarnya telah banyak studi dilakukan guna menanggulangi perilaku radikal dan intoleran dengan berbagai pendekatan: sosial, politik, ekonomi, dll. Dalam tulisan ini akan dibahas salah satu tawaran solusi melalui Studi Islam dalam lembaga pendidikan pesantren tradisional. Temuan di lapangan menyatakan bahwa kurikulum yang diterapkan di pesantren menjadi salah satu faktor signifikan dalam upaya deradikalisasi. Hal ini tak lepas dari metode pembelajaran pesantren yang terbuka serta bahan ajar yang beragam sehingga menyebabkan santri terbiasa dengan perbedaan.]